Patients' Experiences of Telemedicine for Their Skin Problems: Qualitative Study - Aloysius Chow; Sok Huang Teo; Jing Wen Kong; Simon Lee; Yee Kiat Heng; Maurice van Steensel; Helen Smith (JMIR Publications, 2022)
BackgroundTeledermatology is a cost-effective treatment modality for the management of skin disorders. Most evaluations use quantitative data, and far less is understood about the patients' experience. ObjectiveThis qualitative study aimed to explore patients' perceptions of a teledermatology service linking public primary care clinics to the national specialist dermatology clinic in Singapore. A better understanding of patients' experiences can help refine and develop the care provided. MethodsSemistructured in-depth interviews were conducted with patients who had been referred to the teledermatology service. The interviews were digitally recorded and transcribed before undergoing thematic content analysis. ResultsA total of 21 patients aged between 22 and 72 years were recruited. The following 3 themes were identified from the data of patients' experiences: positive perceptions of teledermatology, concerns about teledermatology, and ideas for improving the teledermatology service. The patients found the teledermatology service convenient, saving them time and expense and liberating them from the stresses incurred when making an in-person visit to a specialist facility. They valued the confidence and reassurance they gained from having a dermatologist involved in deciding their management. The patients' concern included data security and the quality of the images shared. Nonetheless, they were keen to see the service expanded beyond the polyclinics. Their experiences and perceptions will inform future service refinement and development. ConclusionsThis narrative exploration of users' experiences of teledermatology produced rich data enabling a better understanding of the patients' journey, the way they understand and interpret their experiences, and ideas for service refinement. Telemedicine reduces traveling and enables safe distancing, factors that are much needed during pandemics.